Getting to Work on Summer Learning Recommended Practices for Success - Augustine, Catherine H. (RAND Corporation, 2013)
RAND is conducting a longitudinal study that evaluates the effectiveness of voluntary summer learning programs in reducing summer learning loss, which contributes substantially to the achievement gap between low- and higher-income students. Based on evaluations of programs in six school districts, this second report in a series provides research-based advice for school district leaders as they create and strengthen summer programs.